Development of high yielding bread wheat variety UAS 375 for timely sown rainfed conditions of the Peninsular Zone of India - Naik, Rudra V; Desai, Shreenivasa Anantharao; Biradar, Suma; Kamatar, Mallikarjuna Y; Singh, Sanjay Kumar; Sudha, Thippeswamy; Patil, Prakashgouda V (Journal of Cereal Research, 2018)
The bread wheat variety UAS 375 was released by Central Subcommitteeon Crop Standards, Notification and Release of variety, Ministry of Agriculture, Govt. of India vide. S.O. 1379(E) dated: 27.03.2018 for cultivation in the Peninsular Zone of the country comprising states of Maharashtra and Karnataka. UAS 375 has recorded an average yield of 21.4q/ha with a potential yield of 29.1q/ha. It has shown yield superiority of 14.4% over the best check variety NI 5439 (18.7q/ha) during three years of testing under timely sown, rainfed conditions. The variety UAS 375 has shown resistance to prevalent pathotypes of stem and leaf rusts in the target environments and has a combination of Lr13+1+ and Sr7b+2+ genes for diversified gene deployment against these rusts. It has better grain, product as well as nutritional quality parameters which makes it preferable variety for product developments. High yield potential of the variety UAS 375 under rainfed conditions coupled with disease resistance and quality traits makes it a suitable choice for the wheat growing farmers of Peninsular India.Â DOI:10.25174/2249-4065/2018/81917